A comprehensive assessment of Hveragerði's geothermal district heating system via thermohydraulic modeling and simulation - Corey Scott Harpe 1995- (2022)
Hveragerði, a town in southwest Iceland, has an immense geothermal resource beneath its feet that has led to a rich history in direct utilization to provide heat and thermal energy to power lives, homes, industries, and greenhouses. However, at its current juncture, Hveragerði’s closed-loop district heating system is stretched to capacity regarding the spread of elevations it can supply, piping network flow capacity, and the available pumping power at the primary heat exchange station. In addition, several operational and maintenance issues have arisen from the direct heating utilization of a high-temperature geothermal reservoir and varying jurisdictional ownership and investment. To address these issues, a comprehensive thermohydraulic computer model was constructed in Fluidit Heat to replicate the function and design of Hveragerði’s district heating system to a high degree of accuracy. In the modeling and simulation process, scenarios were built to model the system's state in January 2022, the future state of the system in January 2030, and to support the optimal design of the district heating system. The critical result of this analysis is a proposal to build three new auxiliary booster pump stations to create a total of four pressure zones over the current one pressure zone system. Additionally, optimal control settings and specifications for future equipment are presented, enhanced modifications to the system are recommended, and key planning topics for the utility owner, Veitur, are addressed. Hveragerði er þekkt fyrir jarðhita, eins og nafnið gefur til kynna. Það er gríðarlegar jarðhitaauðlindur í kring og undir fótum Hvergerðinga. Þessar auðlindir hafa leitt af sér ríka sögu í beinni nýtingu jarðhita, allt frá því að baka brauð og til margskonar iðnaðar og húshitunar. Í Hveragerði eru tvær tegundir af hitaveitu; lokað hringrásarkerfi og gufuveita. Flest almenn hús og híbýli eru tengd lokaða hringrásarkerfinu. Mikil uppbygging hefur átt sér stað í Hveragerði og er því lokaða hitaveitan því komin að ...